Integração interfuncional entre Contabilidade Gerencial e Marketing em uma cooperativa de café - Braga, Josele França e (2023)
The coffee market portrays an extremely competitive, technological, unstable, and dynamic environment, directly affecting organizations that seek to adapt through different strategic plans and internal structures. A company is organized by various elements that perform numerous interconnected functions. These functions vary from company to company, being conditioned to some personal and organizational factors. Among such functions are Management Accounting and Marketing, whose literature on their integration differs in relation to their effectiveness. In this sense, this research sought to understand how the interfunctional integration between Management Accounting and Marketing occurs in a coffee cooperative, in light of the Contingential Theory. For this purpose, a single case study was carried out in a coffee cooperative in the Cerrado Mineiro Region, a region of national and international reference in the production and marketing of coffee. Data was collected by means of semi-structured interviews with employees of both functions, document analysis, and direct non-participant observation at the administrative headquarters of the “Cooperative”. The data were verified by means of Content Analysis. The IRAMUTEQ software was used to treat the data from the semi-structured interviews. The findings showed the existence of cross-functional integration between Management Accounting and Marketing in the structure of the “Cooperative”, mainly due to compliance with budgetary guidelines, based on responsibility and risk management. It occurs by sharing information and involvement between functions through periodic meetings, composed of multidisciplinary teams; by the use of technology (such as integrated software and communication media); by a strategic vision of the market focused on the cooperative member, based on the use of accounting-managerial artifacts of planning and control (by the Budget and Strategic Planning) and marketing strategies (by sales; advertising and communication; events; programs and socio-environmental and sustainable projects and Relationship Marketing). Two patterns of interfunctional cooperation were identified: the "Traditional" (predominant) and the "Transitional". Besides the contingential factor "structure", "strategy", "technology" and "environment" were identified as influencing the integration and the decision-making process and management of the cooperative. The research contributes to the literature by expanding knowledge in the areas of Administration and Accounting, by addressing the interfunctional integration between Management Accounting and Marketing in cooperatives. The findings of this study also contribute by offering insights to the managers of cooperatives and other organizations about the need to recognize and manage interfunctional integration, either by the way information is shared, planned and carried out, and/or through the involvement between the agents of these functions, avoiding conflicts and generating better organizational results.